TEACHERS' PERCEPTION ON THE APPLICATION OF THE GASING METHOD IN LEARNING MATHEMATICS AT ELEMENTARY SCHOOLS IN MANGGARAI - Mariana Jediut; Fransiska Jaiman Madu; Sabina Ndiung; Maria Diana Tilan; Yohanes Indra Purnama (Program Studi PGSD Universitas Flores, 2025)
Motivated by the poor numeracy skills of primary school students in Manggarai Regency, this study examines teachers’ perceptions and experiences of implementing the Gasing method in mathematics classrooms, unlike previous studies that focused mainly on its impact on learning outcomes. The study aimed to describe teachers’ perceptions of using the method in the Langke Rembong sub-district. A descriptive qualitative approach was employed, with data collected through interviews and questionnaires; qualitative data were analysed using the Miles and Huberman model, while questionnaire data were analysed by percentage. The results indicate that most teachers perceive the Gasing method as effective in enhancing quick counting skills and understanding of basic mathematical concepts, although challenges remain in terms of limited training, diverse student readiness, and time constraints. These findings highlight the importance of teacher roles and institutional support in sustaining learning innovations, and suggest that the Gasing method has potential as an effective strategy for improving numeracy instruction in primary schools.